Media Pembelajaran Dua Dimensi Dalam Pembelajaran Fisika - Parinduri, Sri Handayani (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2024)
This research aims to explain the benefits of two-dimensional learning media in increasing students' interest and learning outcomes in physics. The method used in this research is a qualitative method. The data collection technique was carried out by means of triangulation (combination) in the form of a literature review by collecting data, especially verbal data through books, articles, notes and various other scientific literature. The research population was all students of the Padangsidimpuan Campus Private High School. The research sample was class X students at the Padangsidimpuan Campus Private High School. The instruments used to determine the benefits of two-dimensional learning media in increasing students' interest and learning outcomes in physics are questionnaires and multiple choice tests. The research results showed that there was an increase in students' interest and learning outcomes in physics after using two-dimensional learning media